Tutoria centrada na leitura de livros: uma alternativa para alunos com dificuldade em leitura e escrita. - Pasian, Mara Silvia (2004)
Nowadays, there is considerable research into the methods and teaching strategies, offered outside the regular classroom, to help children who are having difficulty learning to read and write. The results of this research indicate that few of these methods and teaching strategies result in significant and lasting effects. The method whereby the teacher offers one-to-one tutoring to the child, based on reading story books has shown positive effects regarding the development of reading and writing skills in children with learning difficulties. The aim of the present work is to investigate the impact of a one-toone, 4 days per week tutoring program, based on reading and writing stories, on the literacy skills of young children with learning difficulties. The effects were evaluated by noting the children's performance before and after the intervention, and by comparing their performance with that of children of average and above average performance in the regular classroom. This research focused on four children in the 2nd year of a public school of the city of São Carlos, who displayed lower performance in reading and writing when compared to their classmates. These 8 year-olds were chosen on the basis of teacher recommendation and scores obtained from the Diagnostic Survey developed by M. Clay. The children s scores were measured before and after the intervention. Interviews with the teachers, regarding the children's performance in the classroom, were carried out before and after the intervention. The activities employed during the tutoring program were: re-reading familiar stories, independent reading of the same story the next day, the identification of single letters or words using magnetic letters, the child making up a story with emphasis on the sounds of words, the cutting up and reassembly of a story, the introduction and reading of a new book. In the case of two of the children, the results showed a significant improvement in their reading and writing skills. After the intervention, the performance of these individuals was equal to the class average, thus enabling them to keep up with their classmates. The reading and writing skills of the other two children also showed significant improvement, though their performance remained below the class norm. These results clearly demonstrate the effectiveness of reading recovery programs in improving the literacy skills of children with learning difficulties.